Design, Analysis and Selection of Planar Parallel Mechanisms - Vijay, P; A. Srinath, Dr; Sri Naga Venkat, P; Ranganath, L; Appalaraju, P (International Journal of Engineering and Technology, 2018)
This paper presents the application of methodology for ten bar single degree mechanisms and selecting the best among them at the conceptual design stage itself. This saves lot of time for one wants to carry away analysis for getting desired output of the mechanism at the design stage. The methodology has been applied to Tiscler robot hands successfully and has obtained the best mechanism in motion distribution among the links of the chain.Â
Keywords: Mechanisms; Robot Manipulator; designing; function generation; motion.